Study on the structure of jumping techniques in aerobic gymnastics - Takeuchi, A.; Nakamura, T. (Japan Journal of Physical Education, Health and Sport Sciences, 2023)
This study referenced Kaneko's notation theory of techniques and clarified the necessary bases for grasping the structure of jumping techniques in aerobic gymnastics. Kaneko's notation theory contains basic words that capture the structural outline of the techniques as well as prescriptive words that capture the structural details of the techniques. The theory involves analysis from a dual perspective, i.e. the goals that must be achieved and the technical skills that are needed to reach those goals. We decided to rely on Kaneko's notation theory because structural studies play an important role in grasping the essence of techniques. It was found that in terms of basic exercise words, "standing" and "sitting/lying" were required to grasp the challenging structures of the starting and landing postures. The words "jump", "twist", and "turning" were shown to be indispensable for grasping the challenges of the jumping techniques. In terms of prescriptive words, it became clear that the base requires "posture" and "face", words that clarify the body alignment and the position in the air with respect to the apparatus. Furthermore, the study revealed that it is necessary to establish a base word, "axis deviation", for techniques that require twisting on an oblique axis, a unique technique in aerobic gymnastics that is not an aspect traditional gymnastics. By clarifying the challenges of the various techniques in this way, we believe that the study has established a premise for systematizing the jumping techniques of aerobic gymnastics.